REPERE TEORETICE ALE MONITORIZĂRII ANGAJĂRII ÎN CÂMPUL MUNCII A ABSOLVENȚILOR INSTITUŢIILOR DE ÎNVĂŢĂMÂNT SUPERIOR - Lilia SPÎNU (Moldova State University, 2018)
În acest articol sunt examinate abordările şi experienţele privind angajarea în câmpul muncii a absolvenţilor instituțiilor de învățămînt superior. În acest context, sunt analizate semnificațiile conceptelor de monitorizare din perspectivă educațională și managerială și monitorizarea angajării în câmpul muncii. THEORETICAL LANDMARKS OF MONITORING EMPLOYMENT IN THE WORKPLACE OF GRADUATES OF HIGHER EDUCATION INSTITUTIONS This article examines approaches and experiences regarding the employment of graduates of higher education institutions. In this context, are analyzed the significance of the monitoring concepts from the educational and managerial perspective and the monitoring of the employment in the workplace.